Exhalation Spreading During Nasal High-Flow Therapy at Different Flow Rates. Issue 7 (8th April 2021) - Dellweg, Dominic; Kerl, Jens; Gena, Amayu Wakoya; Alsaad, Hayder; Voelker, Conrad
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Severe acute respiratory syndrome coronavirus 2 is transmitted through aerosols and droplets. Nasal high-flow therapy could possibly increase the spreading of exhalates from patients. The aim of this study is to investigate whether nasal high-flow therapy affects the range of the expiratory plume compared with spontaneous breathing. DESIGN: Interventional experiment on single breaths of a healthy volunteer. SETTING: Research laboratory at the Bauhaus-University Weimar. Subjects: A male subject. INTERVENTIONS: Videos and images from a schlieren optical system were analyzed during spontaneous breathing and different nasal high-flow rates. MEASUREMENTS AND MAIN RESULTS: The maximal exhalation spread was 0.99, 2.18, 2.92, and 4.1 m during spontaneous breathing, nasal high-flow of 20 L/min, nasal high-flow of 40 L/min, and nasal high-flow of 60 L/min, respectively. Spreading of the expiratory plume in the sagittal plane can completely be blocked with a surgical mask. CONCLUSIONS: Nasal high-flow therapy increases the range of the expiratory air up to more than 4 meters. The risk to pick up infectious particles could be increased within this range. Attachment of a surgical mask over the nasal high-flow cannula blocks the expiratory airstream.